Influence of fallow and tillage types on the indicators of fertility and productivity of winter rye in the long-term experience - N. A. Pegova (Аграрная наука Евро-Северо-Востока)
Long-term use of moldboardless tillage has reduced the yield of winter rye by 0.66 t/ha compared with moldboard tillage (2.77 t/ha) in a field experiment (the beginning of the second rotation). In the lower part of the arable layer (10-20 cm) nitrification capacity decreased by 0.76 mg / kg, exchangeable potassium content - by 44 mg/kg, soil moisture - by 3.2%, bulk density increased up to 1.29 g/cm3, the density of productive stalks decreased by 22.1%, weed infestation increased by 2.3 times. The combined system (plowing in the fallow after four years of moldboardless treatment) at fertility indicators equal to moldboard system has reduced grain yield by 0.27 t/ha due to the thinness of productive stalks by 10% and increase the air-dry mass of weed component in the biocenosis by 12%. Entering of manure into fallow and a clover green-manure fallow have provided the greatest yield of winter rye - 2.59 and 2.61 t/ha for the whole experiment at the expense of increasing of the soil nitrification capacity by 36 and 83%, larger content of exchangeable potassium by 52 and 29%, increase plant density by 35 and 11 pcs./m2. In the control without fertilizers productivity was 2.42 t/ha. At manure plowing the yield of winter rye grain was 3.17-2.69 t/ha; at surface sealing of manure, its effectiveness has decreased by 33-57% (2.02 t/ha) due to highest weed infestation - 215.8 g/m2. Reduce of rye yields after mustard green manure fallow up to 2.22 t/ha was due to the thinness of productive stalks. In the sum of indicators, the cultivation of winter rye is most effective after clover green manure fallow on background of moldboard tillage and spring fertilizing with ammonium nitrate. Thus the yield was 2.98 t/ha, the energy efficiency ratio = 2.53.